Constructivism Analysis of Mandailing Coffee as a Coffee Brand Known in the World - Ikbal Harun; Syafruddin Pohan; Dewi Kurniawati (Journal of Social Interactions and Humanities, 2023)
This research is to describe how mandailing coffee is the most targeted coffee in the international market, using in-depth analysis and interviews with several people who certainly already have knowledge related to mandailing coffee. In this study, of course, applying qualitative methods with a phenomenological approach to the world-known mandailing coffee brand, even though coffee development is not in the first mandailing but in several other regions it has been done a lot. However, how is mandailing coffee the target in the international market? This research will certainly make observations first to map each location to be studied in the field and at the same time make observations at the research location, the informants who become resource persons are of course those who already have involvement in mandailing coffee which has been quite long and years in the coffee world. Documentation of the research to be carried out so as to provide a clearer picture to the reader so that they get a clearer picture apart from the explanation that the researcher describes from the writing by the researcher. After the data is collected, researchers will analyze data from research that has been carried out starting from data reduction to selecting and select data that has been collected, either recorded through the field or obtained during interviews, that data presentation, and conducting a series of information organization and a complete narrative form picture which will certainly make this research conical, To draw conclusions from all research results conducted by researchers so as to provide a systematic explanation in accordance with the formulation of the problem that has been ram bunched.